The proton-pickup reactions as a means to study the spin-polarization and the magnetic moments in 35,37K - Mertzimekis, T. J.; Mantica, P. F.; Davies, A. D.; Liddick, S. N.; Tomlin, B. E. (HNPS Advances in Nuclear Physics, 2019)
Spin polarization in fragmentation reactions has been studied in several nuclei showing mainly that large polarization is produced at the tail of the fragments momentum distribution. Such polarization features are not so well known in pickup reactions, especially in studies of unstable nuclei, such as 35K and 37K. The spin polarization of 35K and 37K produced in single-proton pickup reactions at intermediate energies at the Coupled Cyclotrons at NSCL and the results for the ground-state magnetic moment involving the /3-NMR technique are reported in the present work.